Four‐dimensional computed tomographic angiography of an arteriovenous fistula in the neck. (5th August 2013) - Fujimura, Shintaro; Hori, Ryusuke; Hamaguchi, Kiyomi; Okanoue, Yusuke; Wakizaka, Hitomi; Shoji, Kazuhiko
Abstract : Arteriovenous fistula (AVF), a type of vascular anomaly, is a relatively uncommon disease characterized by abnormal connections between the arterial and venous systems. Recently, remarkable advances in four‐dimensional computed tomographic angiography (4D‐CTA) have enabled detailed analysis of the hemodynamic features of vascular anomalies, which cannot be achieved by conventional imaging modalities. We report a case of AVF in a 59‐year‐old female presenting as a right neck mass. Using reconstructed animations from various viewing angles, 4D‐CTA could clearly visualize not only a mass but the feeding artery and draining vein from the mass. 4D‐CTA was useful for the diagnosis of AVF and to determine the surgical strategy preoperatively. Laryngoscope, 123:2723–2727, 2013